A laboratory-based leak noise simulator for buried water pipes. (1st January 2022) - Iwanaga, M.K.; Brennan, M.J.; Almeida, F.C.L; Scussel, O.; Cezar, S.O.
Graphical abstract: Highlights: Development of a bench-top device to simulate leak signals from buried water pipes. Computational implementation of a mathematical model to generate leak signals. Reproduction of measured leak signals with a laboratory device. Design of filters to compensate for the dynamic effects of the actuators. Abstract: Acoustic correlators are often used to pinpoint leaks in water distribution systems. Generally, these devices are tested for their efficacy in bespoke test rigs that are also used for training purposes. However, this can be problematic as it is difficult to expose the correlators to identical conditions, and only a limited number of situations is possible. An alternative approach is described in this paper, in which a bench-top device, called a leak noise simulator (LNS), is used to generate pipe vibration representative of measured leak noise. The LNS comprises a computer to generate and supply the signals, a dual channel power amplifier and two electrodynamic shakers and accelerometers to generate and measure the vibrations. There are two modes of operation. One involves the generation of leak noise signals using a theoretical model of the buried water pipe implemented in the computer, and the other replicates measured signals from the field that are stored in the computer. To faithfully replicate the pipe vibration due to leak noise, the dynamic effects of the power amplifier and shakers are compensated for by using a filter implemented in the computer. The design and testing of the LNS in both modes are reported in detail, demonstrating the potential of the device.